Standarisasi CSR sebagai kewajiban hukum di Indonesia - Sabela (Fakultas Hukum Universitas Riau, 2014)
Indonesia has applied mandatory CSR as the way to strengthen the implementation of CSR in Indonesia.mandatory CSR applied for only companies whose operating in the field of natural resources.CSR funds in Indonesia are really potential to be managed properly for the benefits of relevant stakeholders and to support the national economic growth.Huge potential CSR funds in Indonesia should be managed by providing transparent and accountable policies.Currently, there is no mandatory CSR guidelines being used by companies who operating in natural resources or related to natural resources.Most of the companies are referring to international CSR guidelines or policies which are voluntary basis.The mandatory CSR legal provision is able to support local economic and providing alternative funding sources for cooperatives, micro, small and medium enterprises when it is well managed and regulated.